PENGARUH STRUKTUR KEPEMILIKAN, STRUKTUR MODAL, PROFITABILITAS TERHADAP NILAI PERUSAHAAN DENGAN KEBIJAKAN DIVIDEN SEBAGAI MODERASI - Wiwit Setyawati (Universitas Pamulang, 2019)
The research was purposed to find out the effect of Ownership Structure, Capital Structure, Profitability to Firm Value and dividend policy as moderating variable. This research uses secondary data of mining companies which are listed in Indonesian Stock Exchange during the years of 2011 - 2015. The sampling technique used purposive sampling. The results showed that the ownership structure has no influence to firm value, the capital structure has a significant negative influence to firm value, and profitability has a significant positive influence to firm value. Dividend policy as a moderating variable weakens influence of institutional ownership, Government ownership and capital structure to firm value. While the influence between profitability and firm value, dividend policy can strengthen its influence. Only profitability have a significant positive influence to firm value. This means high profitability can provide value added to the firm value as reflected by the increasing value of Tobins Q.